1983
DOI: 10.1200/jco.1983.1.11.701
|View full text |Cite
|
Sign up to set email alerts
|

High-dose VP-16-213 and autologous bone marrow transplantation for refractory malignancies: a phase I study.

Abstract: VP-16-213, a congener of epipodophyllotoxin, is a useful chemotherapeutic agent especially against small-cell carcinoma of the lung, germ cell carcinoma, and lymphoma. The standard dose of this drug is limited by myelosuppression. Autologous transplantation of cryopreserved bone marrow assures the restoration of hematopoiesis after marrow ablative cytotoxic therapy. By using this technique, VP-16-213 was dose-escalated using a Fibonacci scheme from the previous highest dose administered to humans (1,500 mg/m2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Other side-effects are hepatic and pulmonary toxicity, especially in extensively pretreated patients. [15][16][17][18] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other side-effects are hepatic and pulmonary toxicity, especially in extensively pretreated patients. [15][16][17][18] …”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of high-dose etoposide in advanced hematological malignancies has been confirmed in several studies. [15][16][17] In combination with TBI, high-dose etoposide followed by allogeneic stem cell transplantation resulted in a disease-free survival of 43% and a relapse rate of 32% in patients with advanced leukemia. 28,29 In a comparative study of AML beyond first CR, Bu/Cy showed an advantage without significance in terms of survival, but the TBI/etoposide regimen resulted in less VOD and GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 Where thiotepa and Mel are strongly myeloablative even as single agents, this is not the case for etoposide. [18][19][20] In the late 70's, etoposide was shown to be able to induce remission in 15-25% of patients with AML who had failed to remit after standard regimens used at that time. 21 These experiences led to the incorporation of this drug into the standard induction courses for newly diagnosed AML.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of preconditioning for HD was based on our experience with melphalan in high grade non-Hodgkin's lymphoma autotransplants and the fact that it had been shown to have value in other series of ABMT in HD (Russell et al, 1989;Zulian et al, 1989). It was considered that VP16, known to be an active agent in HD, used at high dose would be of benefit Wolff et al, 1983;Blume et al, 1987;Jagannath et al, 1986;Stewart et al, 1991). All agents for this procedure needed a short half-life if our policy of using non-cryopreserved marrow, which is associated with rapid engraftment and lack of procedural mortality (Carey et al, 1991) (range 19-46).…”
mentioning
confidence: 99%